2020
DOI: 10.1186/s12935-020-01558-4
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of modified Glasgow Prognostic Score in pancreatic cancer: a meta-analysis

Abstract: Background Several studies were conducted to explore the prognostic value of modified Glasgow Prognostic Score (mGPS) in pancreatic cancer, which reported contradictory results. The purpose of this meta-analysis was to summarize and further investigate the correlation between mGPS and overall survival (OS) in pancreatic cancer. Methods A systematic literature search was performed in PubMed, EMBASE, ISI Web of Science, Cochrane librar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…mGPS levels of 1 or 2 were significantly more often associated with poor OS compared to an mGPS level of 0 (mGPS = 1 vs. mGPS = 0, HR = 1.68, 95% CI: 1.25-2.27, p = 0.001; mGPS = 2 vs. mGPS = 0, HR = 1.90, 95% CI: 1.36-2.67, p < 0.0001). Additional further analyses of 12 studies indicated that mGPS values of 1 or 2 correlated with worse OS in patients receiving chemotherapy (HR = 1.45; 95% CI: 1.05-2.02; p = 0.025) and after pancreatectomy (HR = 1.64; 95% CI: 1.25-2.15; p < 0.0001) [59].…”
Section: Mgpsmentioning
confidence: 94%
“…mGPS levels of 1 or 2 were significantly more often associated with poor OS compared to an mGPS level of 0 (mGPS = 1 vs. mGPS = 0, HR = 1.68, 95% CI: 1.25-2.27, p = 0.001; mGPS = 2 vs. mGPS = 0, HR = 1.90, 95% CI: 1.36-2.67, p < 0.0001). Additional further analyses of 12 studies indicated that mGPS values of 1 or 2 correlated with worse OS in patients receiving chemotherapy (HR = 1.45; 95% CI: 1.05-2.02; p = 0.025) and after pancreatectomy (HR = 1.64; 95% CI: 1.25-2.15; p < 0.0001) [59].…”
Section: Mgpsmentioning
confidence: 94%
“…The main advantage of the mGPS is that it utilises two commonly recorded objective measures, making it easy and simple to calculate in a clinical setting. In a meta-analysis of 20 studies, mGPS demonstrated significant overall prognostic power with hazard ratio (HR) of 1.50 for those categorised as high risk by this score versus those with a low risk [ 72 ]. However, most of these studies were conducted in eastern populations, with western population studies showing inconclusive findings (HR: 1.34, p = 0.268).…”
Section: Scoring Systemsmentioning
confidence: 99%
“…Apart from inflammation, the nutritional status is also related to the outcomes of cancer patients [ 16 , 17 ]. The modified Glasgow outcome scale (mGPS) [ 18 , 19 ] and C-reactive protein-to-albumin ratio (CAR) [ 20 ], are based on the two important acute phase proteins in SIR, namely C-reactive protein (CRP) and albumin [ 4 ], and are related to the prognosis of cancer patients. Nevertheless, in many treatment centers, CRP is not included as a routine measurement of patient care, which limits its clinical application [ 21 ].…”
Section: Introductionmentioning
confidence: 99%